Transcriptional Profiling of Belatacept and Calcineurin Inhibitor Therapy in Renal Allograft Recipients. Issue 8 (20th June 2014) - Vitalone, M. J.; Ganguly, B.; Hsieh, S.; Latek, R.; Kulbokas, E. J.; Townsend, R.; Sarwal, M. M.
<x xml:space="preserve">Abstract</x> Calcineurin inhibitor (CNI) use may lead to allograft injury and compromised renal function. Gene expression profiles of 12‐month kidney biopsies from a Phase 3 study of belatacept and a CNI comparator, cyclosporine (CsA), were compared with expression profiles of a set of historical, demographically matched, preimplantation control biopsies. Gene set enrichment analysis was used to test each set of differentially expressed genes (DEGs) for the enrichment of an in vitro‐derived CNI toxicity (CNIT) gene set and published gene sets associated with chronic allograft injury (CAI), immune modulation and tissue remodeling. The unique set of genes differentially expressed in CNI biopsies compared with preimplantation controls was enriched for genes associated with fibrosis, early tubulointerstitial damage and in vitro CNIT. The DEGs from belatacept biopsies were not enriched for the CNIT genes but, instead, exhibited enrichment for gene sets associated with immune response and tissue remodeling. A combined analysis of DEGs across both treatment groups identified select solute transporter and cellular differentiation genes whose expression at 12 months correlated with renal function at 36 months. These results provide mechanistic insights into the reduced CAI and higher renal function observed in belatacept‐ versus CsA‐treated patients.